The Effect of Leadership Style on Creativity and Innovation: Pengaruh Gaya Kepemimpinan terhadap Kreativitas dan Inovasi (Media Akuntansi, 2019)
This research aims to know and develop a good leadership style to employees as a medium for the development of creativity and innovation of employees in PT Multi Sari Sedap bekasi. Applying a good leadership style will lead to increased creativity and employee innovation. This research includes a type of development research that leads to self-development. For the experiment, the researcher came directly to the location of PT Multi Sari Sedap and used the questionnaire sample which was spread as many as 150 sheets and returned 150 sheets with the calculation of data processing usingSPSS.The results showed that, in testing hypotheses I, II, III, especially on the variable leadership included in the category of relatively good and good. Thus the influence of leadership style on creativity and innovation on Pt Multi Sari Sedap is feasible for future researchers